CONVERSATIONAL IMPLICATURE AND FLOUTING MAXIMS IN SHANG-CHI AND THE LEGENDS OF THE TEN RINGS MOVIE - Imanuel, Ivan; Retno Ningsih, Tri Wahyu (Journal of Language and Literature, 2023)
This research intends to discover the conversational implicature, flouting of maxim, and the most dominant maxim flouted. The theory of Grice (1989) was applied to analyse the conversational implicature and cooperative principles. The descriptive qualitative method is used to explain the conversational implicatures and flouting maxim. After analysing the data, we found 26 data of conversational implicature that divided into generalized implicature 14 data and particularized implicature 12 data, while the flouting of maxim is found 26 data, there are 4 data maxim of quantity, 6 data maxim of quality, 7 data maxim of relation, and 9 data maxim of manner that indicates as a flout during the conversation, maxim of manner became the most dominant maxim that flouted with 9 data. From the research, it can be concluded that generalized conversational implicature was appear frequently in the movie than particularized conversational implicature with 12 data, 26 data of flouting maxim was found in the movie with maxim of manner as the most dominant maxim flouted. Conversational generalized implicature happen more in the movie because the speakers believe that the hearer would understand the information without explaining the knowledge of the conversation. Flouting maxim of manner happen because the speakers explaining information unclear and tend to be ambiguous.